Relato de Experiência no Programa Residência Pedagógica - SILVA, Elizama Félix da (2023)
The Final Paper complies with the structural aspects based on Normative Instruction No. 01/2023 of the “Pró-Reitoria de Graduação” of “Universidade Federal do Pará”, which guarantees in an exceptional and temporary way the activities related to the Final Paper, made flexible in consequences arising from the COVID-19 pandemic. Therefore, the semi-annual reports delivered to CAPES, made as result of my work as a scholarship holder of the “Programa Residência Pedagógica” (2022/2024), were used as a requirement for analysis by the evaluation board to comply with the credit. That said, it is noteworthy that the reports produced address the experiences of two semesters of immersion in the Program run by the UFPA/Campus Ananindeua nucleus. Regarding this, I present experiences lived inside and outside the school participating in the program, such as, for example, participation in the “Futuras Cientistas” carried out in partnership between the “Universidade Federal do Pará”, “Secretaria de Estado de Educação do Pará” and the Federal Government. I also present the experiences lived in third grade high school classes divided into three moments. The content of the report addresses the importance of constructing and using a didactic sequence in the teaching-learning process to give meaning to knowledge and contributing to more meaningful learning for students. As a general result of the reflections, I observe great success in applying chemical calculations linked to atmospheric pollution, making chemistry teaching more applicable and attractive for students. Furthermore, I also highlight that my participation as a Resident enabled several challenging situations in the formation of dealing with the classroom, writing reports, producing a booklet, working with research projects and students' life projects.